Etude des représentations versus prise en compte des représentations : un apport traditionnel de la philosophie - Hubert Vincent (Recherches en Éducation)
« Taking care of représentations » is nowadays a kind of slogan among educationalists. Nevertheless, it’s not hard to show that this orientation of pedagogy has its origins in the beginning of the philosophical traditon, and especially in Plato. The famous socratic method called « réfutation » (elegkhos) is able to attest this point. This return to the source of the notion allow, in one hand, to situate this orientation among others, and so to put it into perspective, and, in the other hand, to criticize this orientation by making more way for the spontaneity of activity.